2020
DOI: 10.12788/jhm.3476
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Ward Adaptation During the COVID-19 Pandemic: A National Survey of Academic Medical Centers

Abstract: IMPORTANCE: Although intensive care unit (ICU) adaptations to the coronavirus disease of 2019 (COVID-19) pandemic have received substantial attention , most patients hospitalized with COVID-19 have been in general medical units. OBJECTIVE: To characterize inpatient adaptations to care for non-ICU COVID-19 patients. DESIGN: Cross-sectional survey. SETTING: A network of 72 hospital medicine groups at US academic centers. MAIN OUTCOME MEASURES: COVID-19 testing, approaches to personal protective equipment (PPE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 8 publications
2
59
0
Order By: Relevance
“…Marked reduction of in person visits, stockpile of PPE and use of respiratory isolation units have been reported. Remarkably, in one study 46% of practitioners reported examples of non-COVID-19 diagnoses in patients admitted for COVID-19 evaluation and vice versa highlighting the challenges induced by the virus to the health care system [235] .…”
Section: Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Marked reduction of in person visits, stockpile of PPE and use of respiratory isolation units have been reported. Remarkably, in one study 46% of practitioners reported examples of non-COVID-19 diagnoses in patients admitted for COVID-19 evaluation and vice versa highlighting the challenges induced by the virus to the health care system [235] .…”
Section: Surveysmentioning
confidence: 99%
“…In the third and final subcategory we find surveys targeting both patients and practitioners in a variety of specializations. From remote management of geriatric patients with heart conditions [232] and the effects of NPIs on transplant recipients/donors [233] to the changes adopted by several hospitals in academic centers [235] , hearing and emergency care [231] , [234] . Overall the observations on patients point to the interim efficacy of telemedicine and to high level of awareness about the risk of infection.…”
Section: Surveysmentioning
confidence: 99%
“…The pandemic caused by the coronavirus disease of 2019 (COVID-19) has placed unprecedented strain on hospitals around the world. Recent research on COVID-19 care delivery has focused on challenges related to critical care capacity (ICU beds, ventilators, and providers) 1 and staffing for general medical wards, 2 particularly in the early phase of the pandemic (March–June 2020). 3 This period was characterized by massive surges that overwhelmed health systems in population centers like Wuhan, China 4 or New York City in the USA 5 or entire regions such as Lombardy in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Since its emergence in December 2019, the rapid spread of coronavirus disease 2019 (COVID-19) has necessitated the expansion and transformation of healthcare facilities worldwide to accommodate the constantly increasing numbers of patients. This situation has provided a potential ground for the transmission of nosocomial infections [ 1 ]. Candida auris is a multidrug-resistant fungal pathogen with the capability for nosocomial transmission.…”
mentioning
confidence: 99%